The role of Physical environment in influencing access to medical services by people with disabilities in Kisiizi Hospital, Rukungiri District. - Atuheire, Excellent (Kabale University, 2025)
The study was about physical environment in influencing access to medical services by people with disabilities in Kisizi hospital, Rukungiri District. The specific Objectives of the study included; to find out the ways how physical environment influence access to medical services by people with disabilities in Kisizi hospital, Rukungiri District, to analyze the challenges faced by people with disabilities in their access to medical services by people with disabilities in Kisizi hospital, Rukungiri District and to suggest the strategies to promote people access to medical services by people with disabilities in Kisizi hospital, Rukungiri District. The researcher used the descriptive research design as appropriate for the study because the study was concerned with finding answers to key questions. The Population of this study comprised of all the people with Disabilities, Kisizi hospital staff and Community leaders (120 in total), because they are the basis of the study and this provided the relevant answers to the study questions. Sampling techniques used included purposive and simple rondom sampling. Descriptive analysis was used to determine the proportions and frequency of the variables. The findings revealed that the availability of specialized equipment and facilities within medical settings is crucial for catering to the needs of individuals with disabilities. They revealed that accessible examination tables, adjustable height sinks, and other assistive devices are essential for providing quality healthcare services to patients with varying abilities as indicated by 22% of the respondents. The study findings revealed that effective communication between healthcare providers and patients is crucial for proper diagnosis and treatment hence this accounted for 22% of the respondents. The findings also revealed that ensuring that medical facilities are physically accessible is crucial hence this includes providing ramps, elevators, accessible parking spaces, and wide doorways to accommodate individuals who use wheelchairs or other mobility aids as indicated by 14% of the respondents. The respondents revealed that healthcare facilities can install height-adjustable examination tables that can be lowered for patients who use wheelchairs or have mobility limitations. The physical environment plays a significant role in determining the accessibility of medical services for individuals with disabilities. Factors such as infrastructure design, availability of ramps and elevators, signage, parking facilities, and overall layout impact the ease with which people with disabilities can access healthcare services.